2022
DOI: 10.3390/jof8010089
|View full text |Cite
|
Sign up to set email alerts
|

Anemochore Seeds Harbor Distinct Fungal and Bacterial Abundance, Composition, and Functional Profiles

Abstract: Many plants adapted to harsh environments have evolved low seed mass (‘light seeds’) with specific dispersal strategies, primarily either by wind (anemochory) or water (hydrochory). However, the role of their seed microbiota in their survival, and their seed microbial abundance and structure, remain insufficiently studied. Herein, we studied the light seed microbiome of eight anemochores and two hydrochores (as controls) collected from four provinces in China, using qPCR and metagenomic sequencing targeting bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…This may be attributed to the fact that several EF genera were shared between more than one host plant and between more than one plant family. However, several wild plant seeds shared only two core microbes, and they had unique endophytic microbiota [ 78 ]. Possibly, wild plants acquired their endophytic microbiota from the surrounding soils, and the soil microbiome could enter and be differently distributed within plant tissues, especially for endophytic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the fact that several EF genera were shared between more than one host plant and between more than one plant family. However, several wild plant seeds shared only two core microbes, and they had unique endophytic microbiota [ 78 ]. Possibly, wild plants acquired their endophytic microbiota from the surrounding soils, and the soil microbiome could enter and be differently distributed within plant tissues, especially for endophytic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Of the c. 200 seeds removed from each plant, 50 seeds were used for surface disinfection. The method followed that used for wild plant seeds using ethanol and bleach (Liu et al, 2022). Then, the seeds were surface dried under aseptic conditions and stored at -20 • C prior to DNA extraction.…”
Section: Panax Seed Collection and Surface Disinfectionmentioning
confidence: 99%
“…Spermatophytes dominate the plant kingdom and have developed a special strategy of adapting to harsh environments such as evolving low seed mass with wind or water dispersal mode, or transmitting beneficial seed microbes from plant generation to another (Shade et al, 2017;Liu et al, 2022). Plentiful studies have shown that there are a great diversity of endophytic microorganisms, some of which stimulated seed germination, seedling health and growth (Shade et al, 2017;Orozco-Mosqueda and Santoyo, 2020;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations